Cyclovirobuxine D Induces Apoptosis and Mitochondrial Damage in Glioblastoma Cells Through ROS-Mediated Mitochondrial Translocation of Cofilin - Zhang, Lin; Fu, Ruoqiu; Duan, Dongyu; Li, Ziwei; Li, Bin; Ming, Yue; Li, Li; Ni, Rui; Chen, Jianhong (Frontiers in Oncology, 2021)
Background: Cyclovirobuxine D (CVBD), a steroidal alkaloid, has multiple pharmacological activities, including anti-cancer activity. However, the anti-cancer effect of CVBD on glioblastoma (GBM) has seldom been investigated. This study explores the activity of CVBD in inducing apoptosis of GBM cells, and examines the related mechanism in depth. Methods: GBM cell lines (T98G, U251) and normal human astrocytes (HA) were treated with CVBD. Cell viability was examined by CCK-8 assay, and cell proliferation was evaluated by cell colony formation counts. Apoptosis and mitochondrial superoxide were measured by flow cytometry. All protein expression levels were determined by Western blotting. JC-1 and CM-H2DCFDA probes were used to evaluate the mitochondrial membrane potential (MMP) change and intracellular ROS generation, respectively. The cell ultrastructure was observed by transmission electron microscope (TEM). Colocalization of cofilin and mitochondria were determined by immunofluorescence assay. Results: CVBD showed a greater anti-proliferation effect on the GBM cell lines, T98G and U251, than normal human astrocytes in dose- and time-dependent manners. CVBD induced apoptosis and mitochondrial damage in GBM cells. We found that CVBD led to mitochondrial translocation of cofilin. Knockdown of cofilin attenuated CVBD-induced apoptosis and mitochondrial damage. Additionally, the generation of ROS and mitochondrial superoxide was also induced by CVBD in a dose-dependent manner. N-acetyl-L-cysteine (NAC) and mitoquinone (MitoQ) pre-treatment reverted CVBD-induced apoptosis and mitochondrial damage. MitoQ pretreatment was able to block the mitochondrial translocation of cofilin caused by CVBD. Conclusions: Our data revealed that CVBD induced apoptosis and mitochondrial damage in GBM cells. The underlying mechanism is related to mitochondrial translocation of cofilin caused by mitochondrial oxidant stress.